One hundred key books of bibliographic repertoire in the process of legitimization and institutionalization of physical education and sport in Spain between 1807 and 1938 - Torrebadella Flix, Xavier; Olivera Beltrán, Javier (Revista General de Información y Documentación, 2012)
Throughout this study it will be presented a selection of reference hundred books from the bibliographic repertoire of physical education and sport, which helped to legitimize and institutionalize this academic, social and professional in Spain between 1807 and 1938. The selection has been marked by a battery of six criteria of relevance in the field of physical education and sport: originality of contents and methods, guidance and value of the objective, professional and intellectual significance, impact and social outreach, the dominant ideological and scientific rigor. Based on these criteria presents a chronological classification, a location a hundred themes of each book in relation to the number of criteria met. Next, we address an interpretive analysis of the reference value of these hundred key works of bibliographic legacy of physical education and sport in this period and their contributions in the eight thematic areas distinguished. The individual contributions of authors, from different positions and different professional fields formed and intellectually solid bibliographic legacy and service of the population that has driven to the historical process of social and institutional legitimization of physical education and sport in Spain.